Das Stupsige und das Problem der Definition des per se Akzidenz in Aristoteles, Metaphysik Z 5 - Mie, Fabian Gustavo (2016)
In Metaphysics Z 5, Aristotle discusses definition by addition and comes to accept it for per se accidents. I aim to explain how Aristotle could allow here certain statements by addition as valid definitions without contravening some relevant rules about repetition he established in the Organon, and also how this definition succeeds in blocking the regress he pointed out at 1030b35-1031a1. I conclude that 'snub nose' can be defined by a non-superfluous repetition, which in turn contains an explication of the quality ('snub') along the line of the specification of the general property ('concavity').